2017
DOI: 10.1155/2017/5049532
|View full text |Cite
|
Sign up to set email alerts
|

Omega Class Glutathione S‐Transferase: Antioxidant Enzyme in Pathogenesis of Neurodegenerative Diseases

Abstract: The omega class glutathione S-transferases (GSTOs) are multifunctional enzymes involved in cellular defense and have distinct structural and functional characteristics, which differ from those of other GSTs. Previous studies provided evidence for the neuroprotective effects of GSTOs. However, the molecular mechanisms underpinning the neuroprotective functions of GSTOs have not been fully elucidated. Recently, our genetic and molecular studies using the Drosophila system have suggested that GstO1 has a protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…As mentioned in the introduction, GSTO1 has been shown to be involved in the reactive oxygen species pathway; this finding, while not novel, shows that GSTO1 coexpression in TCGA patient cohorts is able to recapitulate known canonical biological function of GSTO1. In addition, several reports indicate that GSTO1 plays important roles in neurodegenerative diseases (35,36) and inflammation (17,19). This validates our coexpression analysis, and highlights the novelty of our findings.…”
Section: Integrated Transcriptional Profiles Across Cell Lines Revealsupporting
confidence: 89%
“…As mentioned in the introduction, GSTO1 has been shown to be involved in the reactive oxygen species pathway; this finding, while not novel, shows that GSTO1 coexpression in TCGA patient cohorts is able to recapitulate known canonical biological function of GSTO1. In addition, several reports indicate that GSTO1 plays important roles in neurodegenerative diseases (35,36) and inflammation (17,19). This validates our coexpression analysis, and highlights the novelty of our findings.…”
Section: Integrated Transcriptional Profiles Across Cell Lines Revealsupporting
confidence: 89%
“…GSTO1 overexpression in transgenic Caenorhabditis elegans was observed to impart resistance to oxidative stress generated by numerous pro‐oxidants . GSTO1 was also observed to play a major role in neuroprotection against hydrogen peroxide‐induced neurotoxicity by regulating the mitogen‐activated protein kinase signaling pathway . In addition, GSTO1 has been reported to scavenge free radicals generated by inorganic arsenic, monomethylarsonate and dimethylarsonate via regulation of Docosahexaenoic acid (DHA) reduction .…”
Section: Discussionmentioning
confidence: 99%
“…GSTs play an important role in cellular oxidative damage, carcinogens, and drugs. Among the GST classes, several studies have found that the omega class GST (GSTO) is responsible for the detoxification of exogenous stress [11]. Under oxidative stress conditions, GSTO-1 overexpression in Caenorhabditis elegans has been found to increase the resistance to oxidative damage [12].…”
Section: Introductionmentioning
confidence: 99%